PSS/E based placement wind/PV hybrid system to improve stability of Iraqi grid - Nadheer A. Shalash; Yasar N. Lafta (Institute of Advanced Engineering and Science, 2020)
Proper employment of Hybrid Wind/ PV system is often implemented near the load, and it is linked with the grid to study dynamic stability analysis. Generally, instability is because of sudden load demand variant and variant in renewable sources generation. As well as, weather variation creates several factors that affect the operation of the integrated hybrid system. So this paper introduces output result of a PV /wind via power electronic technique; DC chopper; that is linked to Iraqi power system to promote the facilitating achievement of Wind/ PV voltage. Moreover, PSS/E is used to study dynamic power stability for hybrid system which is attached to an effective region of Iraqi Network. The hybrid system is connected to Amara Old bus and fault bus is achieved to that bus and the stability results reflects that settling time after disturbance is not satisfactory. But, it is found that PV/wind generation system influences Iraqi grid stability to be better than that with only PV generation and the latter is better than stability of the grid that is enhanced with only wind generation. These results represent an important guideline for Iraqi power system planner.